Pelatihan dan Pendampingan Kader tentang ASI Eksklusif pada Ibu Hamil di Kecamatan Ubud Kabupaten Gianyar - A.A. Nanak Antarini (Jurnal Pengabmas Masyarakat Sehat, 2019)
Exclusive breastfeeding is breastfeeding only during the first 6 months of a baby's life without other food. The coverage of 6 months of exclusive breastfeeding in 2017 is 31.6% and for Gianyar regency is 39.8% (Bali Province, 2017), for national coverage 46.7%. The recommended intervention plan from the 2017 Nutrition Status Monitoring Report of Bali Province is by increasing the competency of officers related to Exclusive Breastfeeding. The aim is to assess the level of cadre knowledge about exclusive breastfeeding before and after training and assess the level of knowledge of pregnant women about exclusive breastfeeding before and after counseling by cadres. The form of community service activities was in the form of education, namely training and mentoring for cadres and pregnant women about exclusive Asian breastfeeding in the Ubud District of Gianyar Regency. The level of knowledge in cadres, there is an increase in the average value of knowledge before and after the program. The average level of knowledge before counseling is 41.33 while after training is 78.5 and there is an increase in knowledge of 89.93% on average. the average level of knowledge in pregnant women, there is an increase in the average value of knowledge before and after the implementation of the program. The average level of knowledge before counseling was 39, while after being given counseling at 60 and it was seen that there was an increase in knowledge on average as much as 53.84%.Keyword: Level of Knowledge, Exclusive breastfeeding.